Biodegradable masterbatch blends: The implications on thermal conversion and recycling stream of polyethylene - João Vitor Ferreira Duque; Márcio Ferreira Martins; Marcos Tadeu D'Azeredo Orlando (Open Journal of Chemistry - Peertechz Publications, 2020)
In this case report, we are dealing with the implications of blending fossil LDPE with biodegradable masterbatches on the thermal conversion and recycling stream of Low-Density Polyethylene (LDPE). Two types of commercial masterbatch are evaluated against a pure LDPE. The thermal degradation study was carried out by using thermogravimetric analysis guided by X-ray diffraction, ultimate and proximate analyses. When compared with the LDPE pyrolysis, the conversion of the blend of thermoplastic starch and Polyethylene happens in a wider temperature range, involving multi-step reactions. In contrast, the pyrolysis of iron-based-oxo-biodegradable masterbatch leaves behind 30 wt.% of an unconverted mass. Even though the blend of organic additives with fossil polyethylene might aid the biodegradability of plastics disposed of in the environment, some drawbacks should be accounted for the plastic life cycle.